2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20192226
|View full text |Cite
|
Sign up to set email alerts
|

Autologous serum skin test in 250 patients of chronic spontaneous urticaria at tertiary care hospital in Gujarat

Abstract: <p class="abstract"><strong>Background:</strong> Chronic urticaria (CU) is defined as urticaria persisting daily as or almost daily for more than 6 weeks and affecting 0.1% of the population. In chronic autoimmune urticaria, immunoglobulin G (lgG) auto antibodies react to the alpha subunit of the high-affinity lgE receptor (FceR1) on dermal mast cells and basophils, leading to chronic stimulation of these cells. This results in the release of histamine and other inflammatory mediators which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“… 9 Patients with positive ASST had more severe urticaria, more prolonged duration, and more frequent attacks of urticaria and gastrointestinal symptoms than negative ASST patients. 39 On the other hand, there was no significant difference between ASST-positive and ASST-negative patients with CSU regarding total duration and frequency of disease. 40 A recent study in Korea reported that the predicted positivity of ASST decreased with increasing of serum total IgE level and disease duration with a bimodal distribution of two peaks for twenties and sixties.…”
Section: Discussionmentioning
confidence: 86%
“… 9 Patients with positive ASST had more severe urticaria, more prolonged duration, and more frequent attacks of urticaria and gastrointestinal symptoms than negative ASST patients. 39 On the other hand, there was no significant difference between ASST-positive and ASST-negative patients with CSU regarding total duration and frequency of disease. 40 A recent study in Korea reported that the predicted positivity of ASST decreased with increasing of serum total IgE level and disease duration with a bimodal distribution of two peaks for twenties and sixties.…”
Section: Discussionmentioning
confidence: 86%